Flexibility and resilience in equity-centered research: lessons learned conducting a randomized controlled trial of a family-based substance use prevention program for American Indian families - Nancy L. Asdigian; Nicole R. Tuitt; Rhonda Dick; Monica Fitzgerald; Tracy Zacher; Lisa Bear Robe; Carly Shangreau; Raeann Vossberg; Candace Fleming; Nancy Rumbaugh Whitesell (Frontiers in Public Health)
Meaningful and effective community engagement lies at the core of equity-centered research, which is a powerful tool for addressing health disparities in American Indian (AI) communities. It is essential for centering Indigenous wisdom as a source of solutions and disrupting Western-centric perspectives and inequitable and exclusionary research practices. This paper reports on lessons learned implementing an effectiveness trial of the Thiwáhe Glúwašʼakapi program (TG) program (translated as “sacred home in which families are made strong”)—a family-based substance use prevention program—in a post-pandemic era with an American Indian reservation community that has confronted extreme challenges. We describe lessons in six areas (community engagement, study design, community workforce, participant engagement, retention, and data collection) that illustrate how conventional Western research practices were adapted in order to conduct authentic, equity-centered research. Key principles gleaned from those lessons are also discussed, including: (a) honoring partnerships and making study decisions collaboratively, (b) considering the implications of decisions for both the scientific value of the study and the community, (c) considering the health and well-being of community staff, (d) being flexible and responsive to changing needs, and (e) approaching work with communities through a strengths-based frame. Insight into the challenges encountered and the solutions developed in alignment with community partners and Indigenous wisdom may strengthen the work of other academic-community partnerships endeavoring to bring culturally relevant, evidence-informed prevention programming to Indigenous communities.